PERILAKU MEROKOK SISWA SMP DI KOTA PEKANBARU (Studi Kasus Siswa SMP di Kota Pekanbaru) - Septriadi, Verdian; Asriwandari, Hesti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
The research present describe the smoke activity by students of Junior High School in Pekanbaru city (study case students of Junior High School in Pekanbaru city). Nowdays smoke activity have done by people in Indonesia, and especially smoke activity was doing by teenagers likes student and kids. Smoke can damaged healthy man althought active or passive smokers.The research use the methode are qualitative methodes that analyze problem research by describe the subject and object conditions based on real fact. This research use location in Pekanbaru City and researcher collect data from books, government regulation, jurnal, mass media, website and deep interview with informan research such as student of Junior High School in Pekanbaru city.The conclusion of this research are the smoke activity by students Junior High School in Pekanbaru City has known from family and their friends. The influence factors are the school friend that can push student to know and try for smoke. And social settings that influence student to get smoke are permissive act parents, friends environment, pshycology satisfied from students that has try for smoke.Keywords: smoke, activity and students.